Connection status aware cost efficient message transmission mechanism in opportunistic networks - Da-peng WU; Pu-ning ZHANG; Ru-yan WANG (Tongxin xuebao)
A novel connection status aware cost efficient message transmission mechanism (CSAMT) was proposed. The presented mechanism constructed a dynamic temporal graph matrix based on historical data stored in the cache of the peers to estimate the connection status. Furthermore, the delay, delivery ratio and overhead together were selected as ob-ject optimizing parameters, and then the preferable relay peers could be distributively chosen by adopting equalization and quantification schemes proposed. Numerical results show that CSAMT mechanism can efficiently reduce overhead for more than 48% while the message delivery ratio and latency are improved also.